Diversity of bacteria nodulating Medicago arborea in the northeast area of Morocco - Kamal Guerrouj (Science Faculty of Chiang Mai University, 2019)
A Polyphasic characterization of 30 bacteria isolated from root nodules of Medicago arborea (Medic tree) plants growing in 3 arid soils of the arid northeast region of Morocco was performed. The phenotypic, symbiotic, and cultural characteristics analyzed allowed the description of a broad physiological diversity among the isolates. The phenogram obtained showed 3 main clusters at a similarity coefficient of 78%. The results obtained suggest that the phenotype of these rhizobia might have evolved for adaptation to the local conditions. The genetic characterization which consisted in a rep PCR using ERIC (Enterobacterial Repetitive Intergenic Consensus) primers showed a great diversity and 3 groups and 8 clusters were delimited at a similarity level of 80%. However, the 16S rDNA sequences showed a perfect identity of all the isolates with Sinorhizobium meliloti published sequences.